Improving Risk Assessment in the European Food Safety Authority: Lessons From the European Medicines Agency - Chatzopoulou, Sevasti; Eriksson, Nélida Leiva; Eriksson, Dennis (Frontiers in Plant Science, 2020)
A recently submitted proposal from the European Commission aims to improve the transparency and the sustainability of the EU risk assessment in the food chain by amending the General Food Law Regulation (EC 178/2002) and a number of other regulations related to the food sector. This proposal is the result of a fitness check of the General Food Law Regulation as well as a response to public concerns expressed by a European Citizens´ Initiative. After a critical evaluation of the proposal, this article addresses the importance of changes in the institutional and regulatory environment in the food chain with respect to the risk assessment procedure. For this purpose, in this paper, the institutional and organizational characteristics of the European Food Safety Authority (EFSA) and European Medicines Agency (EMA) are compared in relation to their risk assessment processes and their level of politicization. It is concluded that the risk assessment process of EFSA would become more effective and less politicized, if some of EMA’s associated institutional structures and methods were adopted by EFSA, beyond the proposed amendments by the Commission.